Aeration and Slow Sand Filter Technology in Drilling Well Water Treatment to Reduce TDS Levels - Zulkarnaen, Muhammad Fauzi; Hatimah, Husnul (Universitas Pendidikan Mandalika, 2024)
The quality of borehole water is often affected by the high content of Total Dissolved Solids (TDS) which can disrupt human health and quality of life. This study examines the effectiveness of the combination of venturi aeration and slow sand filter technology in reducing TDS levels in boreholes in East Lombok, NTB. The priority is the use of venturi aeration and slow sand filtration in an integrated manner as a combined treatment for borehole water, which has not been widely explored in previous studies. This method offers a practical, cost-effective, and environmentally friendly solution to overcome high TDS levels, especially in rural areas and areas with limited resources. These findings provide a new perspective on optimizing water treatment technologies to improve community access to clean and safe water. Sampling was carried out from six different locations and initial TDS levels were measured. The borehole water was treated through venturi aeration for 1 hour to remove dissolved gases and organic compounds, followed by filtration using a slow sand filter to filter fine particles, microorganisms, and other dissolved compounds. The results showed that venturi aeration was able to reduce TDS by 6.8% to 17.9%, while the slow sand filter provided an additional reduction of 3.1% to 8.3%. The combination of these two methods resulted in a total reduction in TDS of 11.3% to 25.8%. The effectiveness of the treatment was influenced by the iron content in the air and the structure of the sand media. Data were analyzed using the ANOVA test to determine the significance of the reduction in TDS.